Effects of Working Capital Management on Firm Profitability in Merchandise Companies in Mogadishu, Somalia - Hassan, Ibrahim Jinow; Ali, Abdullah Ibrahim (IJRDO - Journal of Business Management, 2016)
The purpose of the study was to establish the effects of working capital management on firmprofitability in the merchandise firms in Mogadishu, Somalia. The overall results indicated thatthere was a significant linear relationship between averages collection period, inventorymanagement, cash conversion cycle and firm profitability of merchandise firms in Mogadishu.But there was insignificant relationship between average payment period and the firmprofitability. The conclusions were based on the objectives of the study that working capitalmanagement components had a significantly and positively influence on firm profitability ofmerchandise firms.